Two new species of the genus Centromacronema Ulmer 1905 (Hydropsychidae: Macronematinae) from Brazil - Dias, Everton S.; Calor, Adolfo R. (Zootaxa, 2016)
Centromacronema is an endemic genus from the Neotropics, with distribution ranging from Mexico to southern Brazil. The genus comprises 15 described species, but only two of them have been recorded in Brazil: Centromacronema               auripenne (Rambur 1842) and C. obscurum (Ulmer 1905). Two new species are herein described and illustrated from   Brazil, C. pioneira n. sp. from Serra da Jiboia, Bahia state, including the first description of a female for the genus, and C. poyanawa n. sp. from Serra do Divisor, Acre state.